COMPARATIVE STUDY OF ORAL HYPOGLYCEMIC AGENTS IN TYPE-2 DIABETES OBESE PATIENTS - Konuru, Venkateswarlu; Reedy T, Ram Mohan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objectives: The aim of this study was to evaluate safety and efficacy of oral hypoglycemic agents in obese Type-2 diabetic patients. The objectives are to compare fasting and postprandial blood sugar (PPBS) levels, to compare body mass index (BMI) in all the groups, and to identify glycosylated hemoglobin levels and adverse drug reactions (if present) in all the groups. Method: This is a prospective observational study conducted in care diabetic center over a period of 1 year. All the patients those are receiving only oral hypoglycemic agents continuously over a period of 3 months and BMI â‰¥30 were enrolled. The patients receiving insulin were excluded. Patients were followed over a period of 3 months and were reviewed on visit basis (every 30 days). All the necessary information was collected into the data collection form that includes demographic details (age, gender, etc.), past medication history, current treatment charts, and their relevant laboratory reports (fasting blood sugar levels [mg/dl], PPBS levels [mg/dl], glycosylated hemoglobin A1c [HbA1c] (%), and BMI [kg/m2]). Â Â Results: A total of 395 patients were recruited into the study and the drugs received by the population were found to be metformin+sulfonylureas (33%), metformin+pioglitazone (26%), and metformin+dipeptidyl peptidase inhibitors (DPI) (23%). A significant reduction in HbA1c was seen in all groups of patients. Adverse drug reactions observed were hypoglycemia, pedal edema, and itching distributed to drugs metformin+DPI, respectively. A significant reduction in BMI was seen in patients receiving DPI and BMI was found to be increased in other groups of patients. Conclusion: Overall, three classes of drugs were found to have similar efficacy. Sulfonylureas were commonly associated with hypoglycemia when compared to other drugs and weight reduction observed in dipeptidyl peptidase inhibitors.